Electronically Tunable TISO Voltage-Mode Universal Filter Using Two LT1228s - May Phu Pwint Wai; Winai Jaikla; Surapong Siripongdee; Amornchai Chaichana; Peerawut Suwanjan (International Journal of Engineering and Technology Innovation, 2021)
This study aims to design an electronically tunable voltage-mode (VM) universal filter utilizing commercially available LT1228 integrated circuits (ICs) with three-input and single-output (TISO) configuration. With the procedure based on two integrator loop filtering structures, the proposed filter consists of two LT1228s, four resistors, and two grounded capacitors. It realizes five filter output responses: low-pass, all-pass, band-reject, band-pass, and high-pass functions. By selecting input voltage signals, each output responses can be achieved without changing the circuit architecture. The natural angular frequency can be controlled electronically. The input voltage nodes Vin1 and Vin3 possess high impedance. The output node has low impedance, so it can be cascaded to other circuits. The performance of the proposed filter is corroborated by PSpice simulation and hardware implementation which support the theoretical assumptions. The result shows that the range of total harmonic distortion (THD) is lower than 1%, and that the higher the temperature is, the lower the natural angular frequency is.
Keywords: Analog and Mixed-Signal Circuit Design; Innovative Energy Harvesting Technologies; Advancements in PLL and VCO Technologies